Chlorogenic Acid from Hawthorn Berry (Crataegus pinnatifida Fruit) Prevents Stress Hormone‐Induced Depressive Behavior, through Monoamine Oxidase B‐Reactive Oxygen Species Signaling in Hippocampal Astrocytes of Mice. Issue 15 (11th July 2018) - Lim, Dong Wook; Han, Taewon; Jung, Jonghoon; Song, Yuri; Um, Min Young; Yoon, Minseok; Kim, Yun Tai; Cho, Seungmok; Kim, In‐Ho; Han, Daeseok; Lee, Changho; Lee, Jaekwang
Abstract : Scope: Oxidative stress has been implicated in mental disorders, including depression. Chlorogenic acid (CGA), one of the abundant phenolic compounds in herbs and fruits, has the properties of a natural antioxidant and free‐radical scavenger. Therfore, we investigated the antidepressant‐like effects and active mechanisms of CGA from the extract of Crataegus pinnatifida (CP) fruit. Methods and results: Depression‐like phenotypes were induced in mice by daily injection of stress hormone for 1–2 weeks. The brains of these animals exhibited reduced brain‐derived neurotrophic factor expression and increased astrocytic hypertrophy, which are typical markers of depression in animal models. Stress hormone injection 1) upregulated monoamine oxidase B (MAOB) expression and 2) reduced spine numbers along neuronal dendrites, which indicates synaptic depression. The oral administration of CGA (30 mg kg −1 ) or CP (300 mg kg −1 ) prevented MAOB activation following reactive oxygen species (ROS) production and had an ameliorative effect on depressive behavioral tests (e.g., tail suspension and forced swim tests). In vitro assays performed on cultured C8‐D1A cells revealed that CGA and CP inhibited MAOB activity and ROS production. Conclusion: Our study indicates that CGA and CP extracts prevented depressive behavior and thereby have potential as natural antidepressants. Abstract : Depression, as the most prevalent chronic mental disorder, has an enormous impact on society. It is found in the current study that Crataegus pinnatifida extract and chlorogenic acid act as an antidepressant that reduces oxidative stress by inhibiting MAOB in hippocampal astrocytes in an animal model of stress hormone‐induced depression.